2005
DOI: 10.1128/jcm.43.7.3237-3243.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone Resistance of Nontyphoidal Salmonella enterica Isolates in Northern Taiwan Attributable to Production of CTX-M-14 and CMY-2 β-Lactamases

Abstract: . Sixteen of these isolates belonged to Salmonella serogroup B, nine belonged to serogroup C, four belonged to serogroup D, and two belonged to serogroup E. The majority were from stool cultures. The mechanism of resistance was investigated for eight isolates, including three S. enterica serovar Typhimurium, one S. enterica serovar Wagenia, one S. enterica serovar Senftenberg, one S. enterica serovar Derby, one S. enterica serovar Panama, and one S. enterica serovar Duesseldorf isolate. All eight patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
(42 reference statements)
2
21
0
Order By: Relevance
“…b-Lactamases are the predominant (Arlet et al, 2006). In 2004, Salmonella resistant to extended-spectrum cephalosporins were identified in 43 countries encompassing Europe, Latin America, the USA, Taiwan and the Western Pacific (Winokur et al, 2001;Dunne et al, 2000;Li et al, 2005;Su et al, 2005), and its prevalence ranged between 0 and 3.4 %. This is believed to be the first report of CTX-M type ESBLproducing Salmonella in Kuwait and the UAE, and one of the very few reports on the ESBL-producing Salmonella in the Middle East (Hammami et al, 1991;Moubareck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b-Lactamases are the predominant (Arlet et al, 2006). In 2004, Salmonella resistant to extended-spectrum cephalosporins were identified in 43 countries encompassing Europe, Latin America, the USA, Taiwan and the Western Pacific (Winokur et al, 2001;Dunne et al, 2000;Li et al, 2005;Su et al, 2005), and its prevalence ranged between 0 and 3.4 %. This is believed to be the first report of CTX-M type ESBLproducing Salmonella in Kuwait and the UAE, and one of the very few reports on the ESBL-producing Salmonella in the Middle East (Hammami et al, 1991;Moubareck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ESBL-producing Salmonella was about 17 % with a higher proportion (73 %) of these attributable to isolates from Kuwait. This prevalence is much higher than any reported prevalence rates in Salmonella spp., such as the prevalence of 1.5 % reported in the Taiwan (Li et al, 2005;Su et al, 2005), 1.9 % in the USA (Dunne et al, 2000), 2.4 % in Latin America (Winokur et al, 2001), 0.8 % in Europe and 3.4 % in the Western Pacific region (Winokur et al, 2001). The reason for the high prevalence of ESBL-producing Salmonella in our study may be related to the level of usage of the drug in the community, although we do not have any quantitative data on this.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports of qnr or its homologues encoded by transferable plasmids in Gram-negative bacteria (including Salmonella) highlight the significance of these emerging plasmid-mediated mechanism(s). Besides, qnr-plasmids carry integron and multiple resistance determinants including those of beta-lactams and aminoglycosides (Li, 2005, Cattoir and Nordmann, 2009, Garcia-Fernandez 2009. Occurrence of qnr genes in Salmonella from animals has been so far rarely reported, and no publications have reported qnr genes in Salmonella from laying hens or eggs.…”
Section: A Reported Salmonella Serovars In Human Salmonellosismentioning
confidence: 99%
“…(1). Ceftriaxone resistance among Salmonella spp., however, has been reported worldwide (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), and common resistance mechanisms include the production of plasmid-mediated AmpC b-lactamases and extended-spectrum b-lactamases (ESBLs) (2)(3)(4)(5)(7)(8)(9). A previous study involving 78 clinical isolates of Salmonella spp.…”
mentioning
confidence: 99%
“…The CTX-M genes identified in this study have been previously found among Salmonella spp. (7,9,21), and other mechanisms of resistance or rarer ESBL genes may have been responsible for the 3 other CRO-R isolates (isolates Nos. 1, 2, and 4), which were also cefoxitin resistant.…”
mentioning
confidence: 99%